UPAYA PENINGKATAN HASIL MENTIMUN SECARA ORGANIK DENGAN SISTEM TASALAMPOT - INDAH PERMANASARI; AULIA RANI ANNISAVA (Jurnal Agroteknologi, 2015)
Utilization of organic material in crop farming is one of the methods to exploit the local wisdom in agricultural practice. The research was conducted from June to September 2012 in the research farm, State Islamic University of Sultan Syarif Kasim Riau. The objective of the research was to investigate the effects of organic materials and crop density ? in growth and yield on cucumber. Randomized block design with 2 factors and 4 replications was employed in this study. The first factor consists of three levels organic fertilizer treatments i.e. no fertilizer, poultry manure, and compost of oil palm empty bunch. Second factor comprises of three levels of crop density i.e. 1, 2, and 3 plants per pot).. The results showed that there was significant increase on growth and yield on cucumber with poultry manure treatment compare to that of with compost of oil palm empty bunch. Increasing crop density ? improves the number and weight of cucumber yield per pot, even though, some parameters, i.e. number of leaves, stem diameter, crop dry weight, productive number of branches, cucumber size and cucumber weight per plant were significantly decreased.